Thermodynamic and Thermomicroscopy Study of Atorvastatin Calcium-Succinic Acid Binary Mixtures - Yudi Wicaksono; Budipratiwi Wisudyaningsih; Frida Oktaningtias Widiarthi; Tri Agus Siswoyo (Universitas Gadjah Mada, 2017)
Binary mixtures of pharmaceuticals significantly affect the physical and chemical properties of each component. The aim of this work was to explore the thermal behavior and solid state transformation of binary mixture of atorvastatin calcium and succinic acid. The thermodynamics of binary mixtures of atorvastatin calcium - succinic acid were determined by differential scanning calorimeter. Meanwhile, thermomicroscopy and microstructure were determined by a polarized microscope equipped with a heating stage and camera. The results showed that melting points of atorvastatin calcium and succinic acid respectively were 159.35 and 188.51 °C. The solid-liquid phase diagram of atorvastatin calcium - succinic acid indicates the existence of two eutectic points at 136.57 °C and 120.96 °C respectively on the mole fraction of atorvastatin calcium 0.3 and 0.5. Tamman diagram accurately shows mole fraction of atorvastatin calcium at eutectic point 0.33 and 0.46 respectively for eutectic points 130.0 °C and 134.0 °C. Determination of Jackson’s roughness parameter showed a value of atorvastatin calcium, succinic acid and eutectic mixtures > 2 which indicates that the interfaces of remelting crystals were smooth. Microstructure of remelting crystal of atorvastatin calcium and succinic acid respectively was irregular form and crossed plates. The results of thermomicroscopy of binary mixtures of atorvastatin calcium-succinic acid were consistent with differential scanning calorimetry curves and solid-liquid phase diagram.